2012
DOI: 10.1016/j.kjms.2012.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Bladder management of patients with spinal cord injuries sustained in the 2008 Wenchuan earthquake

Abstract: This study's aim is provide an overview of the patients who suffered spinal cord injury (SCI) after the magnitude 8.0 Wenchuan earthquake, including each patient's demographic and epidemiological characteristics, bladder management status, and quality of life (QOL). We also assessed the relationships between bladder management methods, symptomatic urinary tract infection (SUTI), and QOL. Two years after the 2008 Wenchuan earthquake, a cross‐sectional face‐to‐face survey was conducted on 180 patients with SCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
3
14
0
3
Order By: Relevance
“…An analysis of 35 cases of Wenchuan earthquake survivors with SCI by Liu and colleagues (4) found a similar pattern, with the most frequent aetiology being hit by falling debris from building collapse, followed by falls from a height. Thoracic-level injuries were most common in a study of 180 cases of SCI resulting from the Wenchuan earthquake conducted by Luo et al (5), while cervical injuries were found in only approximately 8%; a majority of victims had American Spinal Injury Association (ASIA) Impairment Scale (AIS) grade C lesions and approximately 23% were classified as grade A.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of 35 cases of Wenchuan earthquake survivors with SCI by Liu and colleagues (4) found a similar pattern, with the most frequent aetiology being hit by falling debris from building collapse, followed by falls from a height. Thoracic-level injuries were most common in a study of 180 cases of SCI resulting from the Wenchuan earthquake conducted by Luo et al (5), while cervical injuries were found in only approximately 8%; a majority of victims had American Spinal Injury Association (ASIA) Impairment Scale (AIS) grade C lesions and approximately 23% were classified as grade A.…”
mentioning
confidence: 99%
“…Previous studies on Wenchuan earthquake survivors with SCI have focused on medical complications, pain, quality of life (QoL), functional status, and social participation (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…[1][2][3] Povrede kičmene moždine i posledična disfunkcija mokraćne bešike u mnogome utiču na kvalitet života ovih pacijenata, kao i na njihov mentalni status u smislu depresivnog ispoljavanja. 4,5 U poboljšanju kvaliteta života ovih pacijenata zikalna terapija zauzima veoma važno mesto, kao jedna od najsvrsishodnijih vrsta terapije. Ovaj rad ima za cilj da to i pokaže.…”
unclassified
“…Com referência ao estudo realizado no sul do Brasil, os dados obtidos de participantes com doenças crônicas apresentaram todos os escores dos domínios de QV menores quando comparados à população em geral (CRUZ et al, 2011). No que diz respeito ao estudo da QV de usuários do cateterismo urinário, outros pesquisadores encontraram dados semelhantes a esse estudo tanto nos menores escores medidos pela WHOQOL-bref (The WHOQOL Group, 1996), como nos maiores escores psicológico (BAMPI; GHILHEM; LIMA, 2008;GIROTTI et al, 2011;PEREIRA, 2012;LUO et al, 2012;SZYMANSKI et al, 2016 (The WHOQOL, 1996). Atender as necessidades humanas básicas no processo saúde-doença, com a garantia de uma melhor QV, é um desafio aos profissionais de saúde.…”
Section: Análise Dos Dadosunclassified
“…................................................................................ 44 Quadro 4 (ANDRADE et al, 2009;CUNHA et al, 2013;SILVA et al, 2015;ANDRADES;FERNANDES, 2016 (OH et al, 2005;PANNEK;KULLIK, 2009;PEREIRA, 2012;AKKOÇ et al, 2013;CHARTIER-KLASTER et al, 2013;CASTEL-LACANAL, 2013;COSTA, 2013). Já em relação aos cuidadores , algumas pesquisas são destinadas ao papel da mulher como mãe cuidadora e pouco retratam a temática (BORZYSKOWSKI et al, 2004;LOPES et al, 2011 LIMA, 2008;CDC, 2009;GIROTTI et al, 2011;PEREIRA, 2012;LUO et al, 2012;VAHR et al, 2013;SZYMANSKI et al, 2016).…”
unclassified